Study on the logistics supplier evaluation based on dynamical set pair analysis. Issue 6 (3rd October 2017) - Ye-Wang, Zhou
Abstract: The logistics supplier evaluation is a key step in supply chain management. The paper analyzes the advantages and disadvantages of traditional supplier evaluation at first and has confirmed the index system of the supplier evaluation from three respects. It determines the weight of every index according to entropy weight. Then dynamical set pair analysis model is set up on the basis of the characteristics of the logistics supplier evaluation. The model offers a new thinking for our overall and objective evaluation to logistics supplier.